Decoding & reconstruction of DVB-T2 signal - Muhammad Fadil bin Mohamed Ariffin (2016)
This report reviews the technologies and processes used by Digital Video Broadcasting - Second Generation Terrestrial (DVB-T2) for passive radar applications and transmission of a Digital Terrestrial Television broadcast. In order to better understand the flexibility and efficiency of DVB-T2, an in-depth study on its transmitter, channel types and receiver is conducted and simulated. The first few sections simulates the ideal DVB-T2 transmission on MATLAB using the Common Simulation Platform (CSP) provided by the DVB Consortium. For this case, the ideal receiver simulated assumes knowledge of the transmitted parameters and hence, will not undergo most decoding processes. Additionally, the CSP is analysed and further modified for simulation of a non-ideal (real-life) DVB-T2 transmission by implementing complex decoding of the received data streams and at the same time, achieving performance similarity to that of an ideal case. The final sections will then analyse the results produced and compare the performance and validity of the implemented non-ideal DVB-T2 system with the ideal DVB-T2 system.